Identifying opportunities for nutrition-sensitive value-chain interventions - de Brauw, Alan; Gelli, Aulo; Allen, Summer L. (International Food Policy Research Institute, 2015)
Although value-chain interventions have historically focused on increasing income for smallholders and other stakeholders along the chain (Hawkes 2013), value chains can also play an important role in determining the availability, affordability, quality, and acceptability of nutritious foods. The nutritional benefits and food-safety risks associated with consuming a particular food can be enhanced or diminished at key points along the value chain.